A paper-based biosensor for visual detection of glucose-6-phosphate dehydrogenase from whole blood. Issue 5 (20th January 2020) - White, Dawn; Keramane, Mehdi; Capretta, Alfredo; Brennan, John D.
Abstract : Paper-based, colorimetric, visual detection of G6PD from whole blood without need for equipment. Abstract : Screening for a deficiency of glucose-6-phosphate dehydrogenase (G6PD) in red blood cells is vital for determining the potentially life-threatening presence of congenital, hereditary or induced hemolytic anemias. In this study, a "sample-to-readout" paper-based point-of-care (POC) colorimetric biosensor was developed for direct detection of G6PD in whole blood by simple visual comparison to a color card. The G6PD paper sensor was highly stable with no observable loss in performance after room temperature storage for at least 6 weeks, and worked equally well at room temperature and 37 °C. The simple printed paper format and the stability of the colorimetric reagents facilitates scalable manufacturing. The ability to utilize well established sample collection and preparation protocols along with a colorimetric visual readout should facilitate future transfer of this proof-of-concept POC biosensor to remote or resource-poor locations.